2001
DOI: 10.1086/318090
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 5 Types ofCryptosporidiumParasites in Children in Lima, Peru

Abstract: Cryptosporidium parvum is usually considered to be the pathogen responsible for human cryptosporidiosis. We genotyped Cryptosporidium in 132 stool specimens from 80 Peruvian children, representing 85 infection episodes, using techniques that differentiate Cryptosporidium species and C. parvum genotypes. Five types of Cryptosporidium were identified: C. parvum human (67), bovine (8), and dog (2) genotypes, C. meleagridis (7), and C. felis (1). Twenty-five (29%) of the 85 infection episodes were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
361
1
19

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 473 publications
(393 citation statements)
references
References 22 publications
12
361
1
19
Order By: Relevance
“…In a previous study of specimens from the same cohort, most cryptosporidiosis in this shantytown was caused by the Cryptosporidium parvum human genotype. However, children also had infections with C. parvum bovine and dog genotypes, C. meleagridis , and C. felis (8). Heterologous immunity may be less effective than homologous immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of specimens from the same cohort, most cryptosporidiosis in this shantytown was caused by the Cryptosporidium parvum human genotype. However, children also had infections with C. parvum bovine and dog genotypes, C. meleagridis , and C. felis (8). Heterologous immunity may be less effective than homologous immunity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, C. parvum is infectious when excreted and can be transmitted directly from person to person; Cyclospora cayetanensis requires a period of time in the environment to sporulate into the infectious form (3), decreasing the likelihood of direct person-to-person spread. Cryptosporidium parvum infects both humans and a variety of mammals (6), and evidence is mounting that non- parvum zoonotic Cryptosporidium species can also infect immunocompetent humans (7,8). Conversely, natural or experimental infection of animals with Cyclospora cayetanensis has not been convincingly demonstrated (9–11).…”
mentioning
confidence: 99%
“…A nested PCR assay targeting the small subunit rRNA gene was performed using the earlier reported primers (Xiao et al 2001). Initial primers Cr18PA: (5 0 -TTCTAGAG CTAA TACATGCG-3 0 ) and Cr18PB: (5 0 -CCCATTTCC TTCGAAACAGGA-3 0 ) amplified a 1.3 kb sequence of 18S-rRNA gene.…”
Section: Nested-pcrmentioning
confidence: 99%
“…However, zoonotic species, such as C. meleagridis, C. felis, and C. canis, and also other genotypes of C. parvum, adapted to varied animal species, have been isolated from patients with cryptosporidiosis and identified by molecular methods 18,21,22,24,29,30 . These findings bring up evidences that different species of Cryptosporidium can circulate in the environment, being potential pathogens for humans and animals; this justify the use of molecular techniques for characterization of Cryptosporidium at species level, for better understanding the epidemiology of cryptosporidiosis in specific areas.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that this species naturally infect different species of birds, and in humans it is more frequently described in HIV-infected patients, although different authors have identified cases of C. meleagridis infection not restricted to immunocompromised individuals 6,22,29 . Among the nine immunocompetent children studied, six cases were associated with infection by C. hominis and three cases by C. parvum.…”
Section: Discussionmentioning
confidence: 99%